2010
DOI: 10.1017/s0263034610000510
|View full text |Cite
|
Sign up to set email alerts
|

New micro-cones targets can efficiently produce higher energy and lower divergence particle beams

Abstract: Small conical targets have been used in high intensity laser target interaction mostly in the context of fast ignition. We demonstrate that when cone targets are shaped appropriately and used with specific interaction conditions, they can produce particle beams of higher maximum energy and number in a lower angular divergence than flat targets. This is relevant to fast ignition, small compact particle beams, medical applications, focused ion and/or electron beam microscopes. This fact carries the potential to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In the last two decades, a lot of target geometries were proposed in order to obtain very energetic protons which can be used to treat cancer [3][4][5][6][7][8]. Some works showed that the interaction of the ultra-high intensity laser pulse with a micro-cone target can generate protons accelerated at energies of tens of MeV with low angular divergence and high laser absorption [9][10][11][12] in the Target Normal Sheath Acceleration and Direct laser-lightpressure regimes. Other papers were devoted to different kinds of cone targets suitable for proton acceleration at energies up to few tens of MeV [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, a lot of target geometries were proposed in order to obtain very energetic protons which can be used to treat cancer [3][4][5][6][7][8]. Some works showed that the interaction of the ultra-high intensity laser pulse with a micro-cone target can generate protons accelerated at energies of tens of MeV with low angular divergence and high laser absorption [9][10][11][12] in the Target Normal Sheath Acceleration and Direct laser-lightpressure regimes. Other papers were devoted to different kinds of cone targets suitable for proton acceleration at energies up to few tens of MeV [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Coupling the improved characteristics resulted from a curved foil with a posterior side proton-rich microdot we expect to obtain a better collimated, higher-energy proton beam. Previous studies on the laser light propagation inside conical targets revealed that the laser is focused at the tip while, at the same time, it interacts with the cone sides, accelerating electrons that are transported to the cone tip, thus enhancing the electromagnetic fields [22], [23], [26]. Figure 2 depicts the maximum energies achieved for all the seven cases studied with electrons energies in black triangles, protons energies in red circles and Al ions energies in green squares.…”
Section: Resultsmentioning
confidence: 96%
“…The hot electron density and temperature in the rear vacuum depend on the target geometrical and composition properties such as target curvature, pulse focusing structures and microdots for enhanced proton acceleration [19][20][21][22][23][24][25][26][27][28]. This paper studies the effects of different target density profiles on the spatial distribution of the accelerated particles, the maximum energies achieved, and the characteristics of the electromagnetic fields using the same laser pulse parameters, corresponding to ones available using short pulse PW lasers like CETAL.…”
Section: Improving the Particle Beam Characteristics Resulting Frommentioning
confidence: 99%
“…Due to the nature of the TNSA process, target geometry manipulation can result in enhanced focus of the accelerated particles over tens of microns at considerably large energy densities [18][19][20][21][22]. Thus, by modifying target geometry parameters-such as foil curvature radius, addition of structures before the target for pulse enhancement and microstructures on the posterior side of the target to augment the proton production -one can influence not only the amount of kinetic electrons but also their temperature [23][24][25][26][27][28][29][30][31][32][33]. With this work we aim to pinpoint the effectiveness the foil curvature variation has on tailoring the peak ion energies reached, the angular spread of the accelerated spectrum and tendencies of the photon distribution, while employing laser pulse characteristics that correspond to petawatt short pulse lasers such as the CETAL facility.…”
Section: Introductionmentioning
confidence: 99%